PENGARUH PENYULUHAN ONLINE TERHADAP PERUBAHAN PENGETAHUAN DAN SIKAP SISWA SMK NEGERI 1 KOTA BIMA MENGENAI TINDAKAN ABORSI PADA TAHUN AJARAN 2020 - Anisa; Syamsun, Arfi; Jumsa, Muhammad Rizkinov (Jurnal Kedokteran, 2021)
Background: Lack of knowledge about safe sexual intercourse can lead to pregnancy. Pregnancy has put adolescents in a situation that is awry, therefore abortion could happen. Abortion is the release of conception before the fetus can live outside the womb. Objective: To determine the effect of counseling on changes in knowledge and attitudes of students of SMK Negeri 1 Kota Bima regarding abortion in the 2020 academic year. Method: This was an analytical pre-experimental study with a pretest-post test group design. The research was held in SMK Negeri 1 Kota Bima. The research was conducted in September - October 2020 with a total sample of 36 students of grade XI majoring in Batik and Craft Textiles. Samples were taken by total sampling. Data analysed using Wilcoxon statistical test. Result: The knowledge before counseling was in the sufficient category, which were 22 people (61.1%) and after the counseling, it turned into a good category, which were 27 people (75.0%). The student’s attitude before counseling showed a positive attitude, where 33 people (91.7%) disagree with the abortion and after the counseling, changes to 100.0%. The results of the test for the knowledge and attitude after pretest-post test showed a significant value, which was 0,000, indicating that there was a significant change based on statistics for the knowledge. Meanwhile, the significant value for the attitude after pretest-post test showed a result of 0,083, indicating that there is no statistically significant change. Keywords: Counseling, Knowledge level, Attitude, Abortion